Kualitas Pelayanan Pembuatan KTP Elektronik di Kantor Dinas Kependudukan dan Catatan Sipil Kota Tangerang Selatan - Syahido Fikri, Jirhan; Djumiarti, Titik; Hayu Dwimawanti, Ida (Journal of Public Policy and Management Review, 2024)
The E-KTP printing service is one of the programs implemented by Department of Population and Ciwil Registration, but in its implementation in South Tangerang City there are still some obstacles that occur, the length of service time does not match what was promised and there are still people who doesn’t own their E-KTP. This research aims to explain the Quality of E-KTP services in Department of Population and Ciwil Registration of South Tangerang City. The research method used was qualitative descriptive research with data collected by using interviews, observation, and documentation. This research is done by using theory of service to examine the problem around service quality. The research shows that the service quality in Department of Population and Ciwil Registration of South Tangerang City.is still not adequate. This result shown from several aspects namely Tangibility and Assurance the unavailability of blank card used for E-KTP, the inadequacy of facilities and infrastuctures,, and the uncertainty of service-time. The inhibiting factor among others are : lack of information from Department Of Population And Civil Registration, people’s unfamiliarity about the new rules, people’s difficulty on doing the online registration. Some of the suggestions that the writer would suggests are, making IKD (digitalized KTP) to be the permanent replacement of E-KTP, standardize the facilities and infrastuctures in every service centre, distribute the information through more medias such as brochure, banner, and leaflet, and provide an offline registration for E-KTP reprinting service in service centre.